Teaterteksten som metaforisk struktur - Elung-Jensen, Peter (Peripeti, 2021)
In his analysis of four different modern playwrights, Peter Elung-Jensen writes about the metaphorical structure. In doing so, he brings the question of poetics to the foreground.